Effect of different culture conditions on the structural diversity of prokaryote communities in the sediment of earth ponds stocked with gilthead seabream Sparus aurata (Linnaeus, 1758). (6th December 2013) - Silva, Yolanda J; Manco, Sónia; Costa, Rodrigo; Rodrigues, Vera; Dias, Jorge; Ferreira, Hugo; Pousão‐Ferreira, Pedro; Almeida, Adelaide; Cunha, Angela; Calado, Ricardo; Gomes, Newton C M
Abstract In this study, we evaluate the use of polymerase chain reaction‐denaturing gradient gel electrophoresis (PCR‐DGGE) for monitoring the effect of different aquaculture practices on sediment prokaryote (Archaea and Bacteria) communities. The effect of initial fish (gilthead seabream Sparus aurata) stocking density on the structural diversity of prokaryote communities of earth ponds bottom sediments was evaluated using PCR‐DGGE after a 5 month grow‐out period. An identical approach was used to monitor the effect of supplying different fish feeds [commercial feed (CD) versus an ecofeed (ECO)]. One additional variable was the use of copper sulphate (CuSO4) as an algicide in some of the experimental rearing tanks. The statistical analyses of prokaryote community profiles showed that the presence of fish in earth ponds significantly influenced the structure of sediment prokaryote communities, when compared with earth ponds without fish, independently of the stocking density. Our results also indicated that the structure of the prokaryote communities of earth ponds supplied with the ECO feed shared a strong similarity with that fed CD. Curiously, the use of CuSO4 in ponds receiving the ECO feed promoted significant differences on the structural composition of the bacterial community, but not on the archaeal community. DGGE molecular fingerprints are suitable for fast evaluation of new management practices in food‐fish production on earth ponds by monitoring shifts on microbial communities in bottom sediments.